(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: An eye examination of a pregnant woman is a mandatory phase of her preparation for delivery, with a special attention given to ophthalmic symptoms and relevant recommendations for delivery management. Purpose: To examine spectral domain ocular coherence tomography (SD-OCT) changes in retinal periphery and to provide grounds for the tactics of preparing a pregnant woman for delivery by performing preventive peripheral laser photocoagulation (PPLP). Material and Methods: A 35-year-old myopic woman at 38 weeks of gestation underwent a routine eye examination (visual acuity assessment, refractometry, tonometry, perimetry, biomicroscopy, and ophthalmoscopy), ultrasound biometry and SD-OCT (Heidelberg Engineering). Results: The patient was diagnosed with mild myopia along with peripheral lattice degeneration and peripheral cystic degeneration of the retina in both eyes and local retinal detachment with atrophic retinal breaks in the right eye. The peripheral vitreoretinal lattice degeneration was arrested and the local retinal detachment was limited by laser-induced chorioretinal adhesions. Conclusion: Spectral domain ocular coherence tomography provides an objective picture of the state of both the macular and the periphery of the retina, and, along with biomicroscopy and ophthalmoscopy, provides grounds for the tactics of care for pregnant women for preventing retinal detachment. The outcome of timely preventive laser treatment allowed us to conclude that the patient had no ocular contraindications to vaginal delivery.